2014
DOI: 10.1128/jcm.02306-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BD Max MRSA XT Assay for Use with Different Swab Types

Abstract: We evaluated the performance of the BD Max MRSA XT assay for use with different swab types. The 90% detection rates (95% confidence intervals) were 387 (97 to 1,551), 877 (238 to 3,230), 986 (183 to 5,287), 1,292 (328 to 5,078), 2,400 (426 to 13,518), and 5,848 (622 to 55,021) CFU/swab for Liquid Stuart, Liquid Amies, dry, Amies Gel without charcoal, ESwab collection, and Amies gel with charcoal swabs (Becton Dickinson), respectively. Amies Gel without charcoal, ESwab collection, and Amies gel with charcoal sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Dry swabs, which were used routinely at the collection site for processing on the GeneXpert test, had not been validated by any of the PCR manufacturers but come at a significantly lower price. Of interest, two independent studies also reported that the BDMAX MRSA test, in addition to the approved Liquid Stuart swabs, can be performed with other swab types, e.g., dry and ESwab with equal performance [21,28]. However, the lack of statistically different detection rates between dry and liquid swabs in our study may have been caused by the relatively low overall detection rate for MRSA despite the large number of patients screened as part of routine admission screening.…”
Section: Discussionmentioning
confidence: 70%
“…Dry swabs, which were used routinely at the collection site for processing on the GeneXpert test, had not been validated by any of the PCR manufacturers but come at a significantly lower price. Of interest, two independent studies also reported that the BDMAX MRSA test, in addition to the approved Liquid Stuart swabs, can be performed with other swab types, e.g., dry and ESwab with equal performance [21,28]. However, the lack of statistically different detection rates between dry and liquid swabs in our study may have been caused by the relatively low overall detection rate for MRSA despite the large number of patients screened as part of routine admission screening.…”
Section: Discussionmentioning
confidence: 70%
“…The latter samples might be misclassified as MRSA in assays relying only on SCCmec rightextremity junction amplification. Indeed, for high MREJ C T values, discrepancies with culture results have been observed when singleplex MRSA assays are used, and the use of a C T value of 34 as the threshold for positivity has been suggested (14). In our study, with low MRSA prevalence, such samples were not rare (21.6%).…”
mentioning
confidence: 71%
“…A total of 255 clinical samples were collected for routine MRSA screening from the nares of patients using anterior nares ESwab (Copan Diagnostics, Murrieta, CA). The use of the ESwab with BD Max assays is outside the claims in the package insert; however, its use with the BD Max MRSA first-generation assay was validated in previous studies (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…Both assays utilize real-time PCR and fluorogenic target-specific hybridization probes to detect the SCCmec right-extremity junction (MREJ) and mecA and mecC genes (20)(21)(22). The BD Max StaphSR assay also detects the nuc gene encoding a thermostable nuclease of S. aureus, which allows the assay to detect all S. aureus, including MRSA (21).…”
mentioning
confidence: 99%